The Effect of Parenting Models and Peer Interaction on Prosocial Behavior Of Grade X Adolescents of SMK Muhammadiyah 02 Pagak - Mugiarum, Tria; Purnamasari, Ica; Listyaningrum, R Anggia (Proceedings Series of Educational Studies, 2024)
The application of the parenting model is considered very important, especially in adolescent prosocial behavior, because the application of the right parenting model to children can provide a stimulus on how to properly form adolescent prosocial behavior which will affect the development of prosocial behavior in adulthood. The tendency of students to behave prosocially can occur from peers who make adolescents behave and behave in the same way as their peers, therefore interaction with peers can also be an encouragement in the development of prosocial behavior of adolescents. This study aims to describe the parenting model, and describe the interaction of peer friendship as well as describe the prosocial behavior of adolescents in class X of SMK Muhammadiyah 02 Pagak. This study uses a quantitative approach with a correlational descriptive research design. The results of this study are (a) the parenting model of class X of SMK Muhammadiyah 02 Pagak is included in the good category: (b) the interaction of adolescent friendship in class X of SMK Muhammadiyah 02 Pagak is included in the good category: (c) the prosocial behavior of adolescents in class X of SMK Muhammadiyah 02 Pagak is included in the category of quite good: and (d) there is a sufficient influence between the parenting model and peer friendship interaction on the prosocial behavior of adolescents in class X of SMK Muhammadiyah 02 Pagak.